2022
DOI: 10.3389/fendo.2022.1003238
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin combined with metformin versus metformin monotherapy for endocrine and metabolic profiles in overweight and obese women with polycystic ovary syndrome: A single-center, open-labeled prospective randomized controlled trial

Abstract: ObjectivesCanagliflozin (CANA), a kind of sodium-glucose cotransporter-2 (SGLT-2) inhibition, study in which the role of CANA monotherapy in polycystic ovary syndrome (PCOS) has been investigated, and it could become a novel option in the PCOS treatment. Nevertheless, trials focused on SGLT-2 combination therapy’s efficacy, and safety in PCOS patients are limited. This randomized controlled trial compared the efficacy and safety of CANA and metformin (MET) combination therapy and MET monotherapy in endocrine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…A study that compared the use of canagliflozin with metformin alone showed no changes in the menstrual cycle, level of FSH, LH, free androgen, androgen-binding globulin, A4, or lipid status. However, there was a significant difference in the reduction of free testosterone, BMI, regulation of glycemic status, and insulin secretion [ 58 ]. Zhang also demonstrated that SGLT-2is reduce lipotoxicity and improve androgen metabolism in PCOS [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study that compared the use of canagliflozin with metformin alone showed no changes in the menstrual cycle, level of FSH, LH, free androgen, androgen-binding globulin, A4, or lipid status. However, there was a significant difference in the reduction of free testosterone, BMI, regulation of glycemic status, and insulin secretion [ 58 ]. Zhang also demonstrated that SGLT-2is reduce lipotoxicity and improve androgen metabolism in PCOS [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a significant difference in the reduction of free testosterone, BMI, regulation of glycemic status, and insulin secretion [ 58 ]. Zhang also demonstrated that SGLT-2is reduce lipotoxicity and improve androgen metabolism in PCOS [ 58 ]. In addition, in obese women with PCOS, canagliflozin therapy in combination with metformin compared to metformin as a monotherapy has similar effects on the menstrual cycle, body weight, and IR, but lowers the free testosterone levels more and has a better effect on glucose metabolism [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with MET monotherapy, CANA/MET may have greater benefits in reducing total testosterone, AUC for glucose, and AUC for insulin over three months. However, more studies are needed to evaluate the long-term effects of SGLT-2 inhibitors in patients with PCOS [3].…”
Section: Treatment Of Irregular Menstrual Cycle and Hyperandrogenismmentioning
confidence: 99%
“…Тaking into account the importance of the correction of metabolic parameters in PCOS, a number of measures of both medicinal nature and non-medicinal means (diet therapy, physical exercise, phytotherapy) are proposed [7,8].…”
Section: Introductionmentioning
confidence: 99%